2021
DOI: 10.35675/befdergi.850653
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Turkish as a Foreign Language According to the Views of Textbook Authors

Abstract: Bu araştırmanın amacı ders kitabı yazarlarının yabancı dil olarak Türkçe öğretimine ilişkin görüşlerini tespit etmektir. Araştırmanın alt problemleri; müfredat, beceri, dil bilgisi ve söz varlığı öğretimine ilişkin yazarların görüşlerini ortaya koyacak biçimde oluşturulmuştur. Nitel olarak tasarlanan araştırmanın çalışma grubunu yabancı dil olarak Türkçe öğretimi alanında ders kitabı yazarlığı yapmış on üç katılımcı teşkil etmiştir. Veriler yarı yapılandırılmış görüşme formu ile elde edilmiştir ve içerik anali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On the other hand, in their study Teaching Turkish as a Foreign Language According to the Views of Textbook Authors, Karagöl and Kurt (2021) revealed the opinions of the coursebook authors on teaching Turkish as a foreign language on the basis of curriculum, skills, grammar and vocabulary teaching. In this study carried out with a group of authors who prepared book sets for teaching Turkish by levels within the scope of formal education based on the "Curriculum for Teaching Teaching Turkish as a Foreign Language" prepared by the Turkish Maarif Foundation, the perceptions and opinions of the authors on the book writing process were determined.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…On the other hand, in their study Teaching Turkish as a Foreign Language According to the Views of Textbook Authors, Karagöl and Kurt (2021) revealed the opinions of the coursebook authors on teaching Turkish as a foreign language on the basis of curriculum, skills, grammar and vocabulary teaching. In this study carried out with a group of authors who prepared book sets for teaching Turkish by levels within the scope of formal education based on the "Curriculum for Teaching Teaching Turkish as a Foreign Language" prepared by the Turkish Maarif Foundation, the perceptions and opinions of the authors on the book writing process were determined.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%